Recovery Jamu Tradisional Menjadi Produk Berdaya Saing Global - Dina Amalia Khoirun Nadha Raswadiyanto; Wahyu Eko Pujianto (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
The purpose of this research is to find out how to improve traditional herbal products so that they can be globally competitive and have enthusiasts who are not inferior to modern medicine. Jamu is a herbal drink used for health. Since ancient times until today, herbal medicine is used as a treatment and prevention of disease. In the current era, product innovation in herbal medicine packaging has the potential to bring back old herbal medicine into a more modern herbal medicine. The problem with this herbal medicine is the lack of marketing and the change from plastic packaging to the latest bottle packaging. From the point of view of young people, dependence on drugs is very dangerous. The necessary solution is to advise jamu traders to follow the latest marketing strategies and change the packaging to be more attractive to consumers. Therefore, jamu is a traditional herbal medicine that should remain. This research was conducted on a resource person selling jamu at a roadside shop in the village of Balongdowo Candi Sidoarjo using qualitative data collection methods with a descriptive approach of interviewing business owners, which aims to find out how the jamu business process has long been operating in the era of ancestors then now competes again in modern times.